I Certamen Crono-Teatro (2013). Modalidad de vagón 2. Cabalgate express - Pygmalión, (Pygmalion. Revista de teatro general y comparado, 2025)
I Certamen Crono-Teatro (2013). Modalidad de vagón 2. Cabalgate express